Chronic Fatigue and Its Impact on the Quality of Health Care. “Chronic fatigue and medical attention” - María Esmeralda González Hernández,; Jesús Carlos Ruvalcaba Ledezma,; Esmeralda Guadalupe Tovar Olvera,; Olga Rocío Flores Chávez,; Claudia Teresa Solano Pérez,; María del Carmen López Zermeño,; Leticia Carolina Hernández Esparza,; osefina Reynoso Vázquez, (Public Health, 2026)
Introduction. Chronic fatigue is a social and professional issue that affects labor, causing poor and constrained medical attention for patients. High demand for labor output from health professionals leads to irritability and depression. This syndrome is usually present in nurses and doctors who work in close contact with other people. Recently, job-related stress due to long work requirements has become one of the major debilitating factors for the mental and physical health of medical students. Aim. Determine the impact of chronic fatigue syndrome on resident physicians and on the quality of medical care. Method. A non-experimental observation was conducted on 50 medical residents of a hospital in Pachuca, Hidalgo, Mexico. Results. 90% of resident physicians report that they work for 30 continuous hours, 10% work 40 hours in three days per week; they show fatigue and emotional distress, people give little importance to rest and sleep well, without imagining the consequences of sleep deprivation and a low in our immune system, low protection and a source of stress. In fact, medical residents are constantly under a special training regime and stressful labor, with academic and working conditions that affect their mood and mental health. Conclusion. Doctors begin the training with a clinical practice legacy of ethical maxims learned by teachers and books, but what happens in practice and daily work, could originate violent emotional shocks